Mueller matrix polarization interferometry of optically anisotropic architectonics of biological tissue object fields: the fundamental and applied aspects - Ushenko, Alexander; Dubolazov, Alexander; Zheng, Jun; Bakun, Oxana; Gorsky, Mykhaylo; Ushenko, Yuriy; Litvinenko, Olexandra; Gordey, Ivan; Zhebo, Chen; Sklyarchuk, Valeriy (Frontiers in Physics, 2024)
The presented results concern the diagnostic application of vector-parameter polarization mapping and polarization-interference phase scanning applied to layered azimuth and ellipticity polarization maps obtained with help of digital holographic reproduction for phase-inhomogeneous tissue layers in the female reproductive system. The differential diagnosis of pathological changes in optically anisotropic polycrystalline tissue components, specifically "benign (fibroids) -precancerous (endometriosis)," was investigated. All studies within the representative groups of histological samples were conducted using circularly polarized laser radiation, ensuring azimuthal invariance and polarization measurements reliability. Integral and layered maps and polarization azimuth and ellipticity random variables distributions histograms were obtained from microscopic images of histological sections from the female reproductive system tumors. Systematized tables present statistical moments which characterize azimuth and ellipticity polarization maps for fibroids and endometriosis tissues. It is shown that statistical parameters (diagnostic markers) are the most sensitive to benign and precancerous changes in the female reproductive system tissues. The results of information analysis, including the accuracy determination of the diagnostic vector-parameter polarization and polarization-interference methods for detecting and differentiating samples of fibroid and precancerous endometriosis tissues in the female reproductive system, are presented.